Peningkatan Kemampuan Peserta Didik Terhadap Baca Tulis Al-Qur'an melalui Guru PAI - Ramayani, Ajeng; Nurzanah, Rizki (DIKLINKO JOURNALS PUBLISHER, 2023)
A single paragraph of about 250 words maximum. For research articles, abstracts should give a pertinent overview of the work. We strongly encourage authors to use the following style of structured abstracts, but without headings: (1) Background: Place the question addressed in a broad context and highlight the purpose of the study; (2) Purpose of the Study: Identify the purpose and objective of the study; (3) Methods: Describe briefly the main methods or theoretical framework applied; (4) Results: Summarize the article's main findings; and (5) Conclusions: Indicate the main conclusions or interpretations.